Government Support, Trust, and UTAUT 2 in Willingness to Adopt & Pay Smart Home Indonesia - Anggoro Ary Nugroho; Imam Salehudin (Jurnal Indonesia Sosial Teknologi, 2024)
Smart home is one of the Internet of Things (IoT) currently developing in Indonesia. The research examines the factors determining Willingness to Adopt and Willingness to Pay to use a Smart home in Indonesia. This study uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2), Government Support, and Trust to examine the relationship of influencing factors. Respondents from the study consisted of 353 people who already owned a house/place to live and did not have a smart home device, which was obtained from an online survey. Analysis of research data using Structural Equation Modeling (SEM) with the help of SMART PLS software. The research results show that Facilitating Conditions, Habit, Government Support, and Trust positively affect Willingness to Adopt Smart homes. Social Influence, Facilitating Conditions, Price Value, and Willingness to Adopt positively affect the Willingness to Pay for a Smart home. This research can provide insight into smart home development in Indonesia.